2011
DOI: 10.1063/1.3598083
|View full text |Cite
|
Sign up to set email alerts
|

Modulation periodicity dependent structure, stress, and hardness in NbN/W2N nanostructured multilayer films

Abstract: NbN/W2N nano-multilayer films with a modulation periodicity, Λ, ranging from 5.1 to 157.4 nm have been deposited on a Si(100) substrate by reactive magnetron sputtering in Ar/N2 mixtures. The Λ dependent structural and mechanical properties for the resulting NbN/W2N multilayers have been evaluated by means of low-angle x-ray reflectivity, x-ray diffraction, high-resolution transmission electron microscope, and nanoindentation measurements. The finding is that for films with Λ ≤ 10.6 nm, fcc NbN layers are cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Many papers that studied different multilayer films have demonstrated that there is an optimal bilayer period that provides the best mechanical properties. For example, TiN/WN coatings showed maximized hardness at Λ = 8.1 nm, and an optimal bilayer period for NbN/WN multilayers was about 7.4 nm, while in both cases, increasing the Λ deteriorated their characteristics. Similar behavior of the WN-based multilayer system was observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many papers that studied different multilayer films have demonstrated that there is an optimal bilayer period that provides the best mechanical properties. For example, TiN/WN coatings showed maximized hardness at Λ = 8.1 nm, and an optimal bilayer period for NbN/WN multilayers was about 7.4 nm, while in both cases, increasing the Λ deteriorated their characteristics. Similar behavior of the WN-based multilayer system was observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the characteristics of WN and NbN, multilayer coatings based on these nitrides should have excellent wear-resistant properties. The only paper on WN/NbN films deposited by magnetron sputtering was published by Wen et al 33 At a bilayer period of 7.4 nm, multilayers demonstrated a hardness greater than 40 GPa, but other properties were not reported. Therefore, we elected to conduct a more in-depth analysis of changes in the microstructure and tribological behavior of WN/NbN coatings upon variations in the deposition parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most published papers on multilayers with tungsten nitride used magnetron sputtering and ion-beam-assisted deposition [10][11][12]. Wen et al [13] studied WN/NbN nanostructured multilayer films with different modulation periods deposited by direct current magnetron sputtering. This system demonstrated superhardness of about 43.7 GPa.…”
Section: Introductionmentioning
confidence: 99%